2017
DOI: 10.1108/ijwis-04-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Improving entity linking with ontology alignment for semantic microservices composition

Abstract: Purpose This paper aims to propose a method based on Linked Data and Semantic Web principles for composing microservices through data integration. Two frameworks that provide support for the proposed composition method are also described in this paper: Linkedator, which is responsible for connecting entities managed by microservices, and Alignator, which aligns semantic concepts defined by heterogeneous ontologies. Design/methodology/approach The proposed method is based on entity linking principles and uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…The LOD cloud (Abele and McCrae, 2017; Assaf et al , 2015) is used to combine distributed and various open data sets into an innovative application, and that it has emerged as one of the largest collections of interlinked open data sets on the internet. In Salvadori et al (2017), the authors propose an approach based on linked data and Semantic Web technologies for composing microservices through data integration.…”
Section: Related Workmentioning
confidence: 99%
“…The LOD cloud (Abele and McCrae, 2017; Assaf et al , 2015) is used to combine distributed and various open data sets into an innovative application, and that it has emerged as one of the largest collections of interlinked open data sets on the internet. In Salvadori et al (2017), the authors propose an approach based on linked data and Semantic Web technologies for composing microservices through data integration.…”
Section: Related Workmentioning
confidence: 99%
“…Extensional-based techniques can be adapted for service enrichment (Salvadori et al, 2017) and, similarly to OntoGenesis, exploit instance data to find ontology alignments. They rely on individuals obtained from data services and from external sources to check if they have some intersecting properties, i.e.…”
Section: Other Ontology Matchersmentioning
confidence: 99%
“…Thus, OntoGenesis constructs ontologies with a flat class hierarchy (without subclasses) and the only relations between classes occur through domains and ranges of properties. Although extensional-based techniques can be adapted for service enrichment (Salvadori et al, 2017), such techniques present poor performance (as shown in section 5.5) when data obtained through the service interface is unrelated to data from the external sources and when individuals are not the same. In light of such evidence, we argue that extensional ontology matching algorithms present distinct characteristics from the problem we tackle, specifically property matches.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations